The manufacturing of puffed corn flakes: Optimization, characterization and sensory attributes - Xu, Na; Yao, Xinmiao; Lu, Shuwen (Emirates Journal of Food and Agriculture, 2023)
Corn snacks are growing worldwide in food market. Puffing is an alternative processing technology to improve the characteristics of food products with the benefit of low oil. However, the puffing process of corn flakes is rarely studied in recent research. Thus, the objective of this study is to optimize the conditions of puffing with the raw material of corn grit and compare with extrusion, frying and baking process in the aspect of microstructure and sensory evaluation of corn flakes. The results showed that the optimized conditions of puffing flakes were 6 min of pretreated time, 226 °C of puffing temperature, 9 s of puffing time. And the experimental responses of crispy, hardness and browning index at the optimized conditions are 0.73±0.05 nm, 1317.52±23.14 g, 56.91±0.87, respectively. To compared with other traditional process that manufacture the corn flakes, the microstructure and sensory evaluation are applied. The microstructure of puffing method presented porous and spongy structure with numerous cavities in small sizes. For the sensory evaluation, the score of taste, texture, color and overall acceptability applied for puffing is the highest. In conclusion, the puffing would be a novel technology to manufacture tasty corn flakes in the snack food industry. Keywords: Corn flakes; Optimization; Puffing; Response surface methodology; Sensory attributes